The priming molecule β‐aminobutyric acid is naturally present in plants and is induced by stress. Issue 2 (26th October 2016) - Thevenet, Damien; Pastor, Victoria; Baccelli, Ivan; Balmer, Andrea; Vallat, Armelle; Neier, Reinhard; Glauser, Gaétan; Mauch‐Mani, Brigitte
Summary: The defense system of a plant can be primed for increased defense, resulting in an augmented stress resistance and/or tolerance. Priming can be triggered by biotic and abiotic stimuli, as well as by chemicals such as β ‐aminobutyric acid (BABA), a nonprotein amino acid considered so far a xenobiotic. Since the perception mechanism of BABA has been recently identified in Arabidopsis thaliana, in the present study we explored the possibility that plants do synthesize BABA. After developing a reliable method to detect and quantify BABA in plant tissues, and unequivocally separate it from its two isomers α ‐ and γ ‐aminobutyric acid, we measured BABA levels in stressed and nonstressed A. thaliana plants, and in different plant species. We show that BABA is a natural product of plants and that the endogenous levels of BABA increase rapidly after infection with necrotrophic, biotrophic and hemibiotrophic pathogens, as well as after salt stress and submergence. Our results place the rise in endogenous BABA levels to a point of convergence in plant stress response and provide biological significance to the presence of a receptor in plants. These findings can explain the extremely widespread efficacy of BABA and open the way to unravel the early steps of priming.